PENGEMBANGAN DISTRIBUSI PEMASARAN IKAN KERING DI KECAMATAN SASAK RANAH PASISIE KABUPATEN PASAMAN BARAT, SUMATERA BARAT - Usvita, Mega; Yunus, Mukhlis (Transpublika Publisher, 2022)
The purpose of this study is to determine the marketing, distribution, and development of dried fish in the Sasak Ranah Pasisie District of West Pasaman Regency, West Sumatra. Techniques for data collection include observation, interviews, and the use of questionnaires, followed by documentation of the data for analysis. The descriptive analysis method was used to evaluate the data obtained in this study. An effective and efficient marketing strategy model that leverages strengths to capitalize on long-term opportunities through product/market diversification, a focus on minimizing internal problems in order to create better market opportunities, and continuous improvement and evaluation of the dried fish business. The strategy for resolving marketing and distribution issues with salted fish in the Sasak Ranah Pasisie is to provide techniques and strategies that enable the products they create to be distributed both regionally and beyond the West Pasaman area. The community is briefed on how to efficiently market salted fish and how to distribute salted fish to various locations with minimal distribution costs. Almost all consumer products are distributed by wholesalers or retailers. Manufacturers can save cost by outsourcing certain marketing operations to intermediaries.